1982
DOI: 10.1073/pnas.79.2.446
|View full text |Cite
|
Sign up to set email alerts
|

Human monoclonal IgM with autoantibody activity against intermediate filaments.

Abstract: Monoclonal IgMs from two patients with Waldenstrom macroglobulinemia were found to react with intermediate filaments. This was shown by (a) immunostaining of various tissues and cultured cells and (b) immunological characterization of the reactive antigen after blotting of polypeptides separated from total cell extracts by gel electrophoresis or purified intermediate filaments on nitrocellulose sheets. One monoclonal IgM had an activity directed only against vimentin, whereas the other reacted with four differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(38 citation statements)
references
References 27 publications
1
36
1
Order By: Relevance
“…8 Even though few of these studies convincingly proved that the observed phenomena were indeed caused by binding of the respective paraprotein to its specific antigenic target (e.g., by ''reverse Western'' blotting or sequencing of the target antigen as done in this study), these selective observations are often cited to support a causal relationship between the development of an MGUS or MM clone and chronic antigenic stimulation. [1][2][3][4][5][9][10][11][12][13][14][15][16] In contrast to these previous reports, our unbiased systematic study did not only convincingly prove the paraprotein-mediated reactivity against the identified antigens, it also revealed a broad spectrum of antigenic targets of paraproteins. The fact that of >6 3 10 8 possible paraprotein/target-antigen interactions screened only 4 were identified as paraprotein-mediated indicates that the antigenic sources tested (which included a large proportion of the expressed human genome as possible sources for autoantigens as well as the major sources for food allergens) represent only a small part of the entire antigenic target spectrum of human paraproteins.…”
Section: Demonstration Of Paraprotein-mediated Reactivitycontrasting
confidence: 99%
“…8 Even though few of these studies convincingly proved that the observed phenomena were indeed caused by binding of the respective paraprotein to its specific antigenic target (e.g., by ''reverse Western'' blotting or sequencing of the target antigen as done in this study), these selective observations are often cited to support a causal relationship between the development of an MGUS or MM clone and chronic antigenic stimulation. [1][2][3][4][5][9][10][11][12][13][14][15][16] In contrast to these previous reports, our unbiased systematic study did not only convincingly prove the paraprotein-mediated reactivity against the identified antigens, it also revealed a broad spectrum of antigenic targets of paraproteins. The fact that of >6 3 10 8 possible paraprotein/target-antigen interactions screened only 4 were identified as paraprotein-mediated indicates that the antigenic sources tested (which included a large proportion of the expressed human genome as possible sources for autoantigens as well as the major sources for food allergens) represent only a small part of the entire antigenic target spectrum of human paraproteins.…”
Section: Demonstration Of Paraprotein-mediated Reactivitycontrasting
confidence: 99%
“…Epitope specificity was also determined by ELISA using recombinant full-length paratarg-7 and recombinant fragments of paratarg-7 as a coat. All 29 paratarg-7 reactive paraproteins were tested by this ELISA and all reacted with recombinant paratarg-7 1-36 and paratarg-7 [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] confirming the epitope specificity obtained with the peptide spot assay (Fig. 4).…”
Section: Antibody-binding Epitope Of Paratarg-7supporting
confidence: 53%
“…15 Even though few of these studies convincingly proved that the observed phenomena were indeed caused by binding of the respective paraprotein to its specific antigenic target (e.g., by ''reverse Western'' blotting and/or sequencing of the target antigen as done in this study), these selective observations are often cited to support a causal relationship between the development of an MGUS or MM clone and chronic antigenic stimulation. [1][2][3][4][5][16][17][18][19][20][21][22][23] Similarly, doubts are raised about the paraprotein-mediated reactions with antigens predicted by epitope reconstruction and reported in a recent paper, 24 because the reactions were observed at concentrations of the paraprotein-containing serum of only 1:2,500. In contrast to these reports, our first systematic studies 7,8 did not only convincingly prove the paraprotein-mediated reactivity against the identified antigens, it also revealed a broad spectrum of antigenic targets of paraproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Gabbiani and associates (4) and Lidman et a1 (19) have suggested that the presence of this anti-actin antibody is diagnostic of chronic active hepatitis. Autoantibodies to INFIL have been noted during acute viral infections and in various malignancies (6)(7)(8)(9)(13)(14)(15)(16). Antitubulin has been reported in sera from patients with autoimmune thyroid disease and with alcoholic liver disease (5,17).…”
Section: Discussionmentioning
confidence: 99%
“…Anticytoskeletal antibodies (ACY) have been reported to occur in various human sera (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). These reports did not establish a significant functional or diagnostic relationship between the presence of particular antibodies and the occurrence of a particular disease.…”
mentioning
confidence: 99%